Global burden and projection of colorectal cancer attributable to low whole-grain diets: an analysis of GBD 2021 data with Bayesian age-period-cohort modeling - Tian, Hongmei; Xie, Xin; Li, Xiaoqing; Pang, Yueshan; Xie, Jiebin (Frontiers in Oncology, 2025)
BackgroundA diet low in whole grains may be a significant risk factor for colorectal cancer (CRC). Therefore, analyzing the latest global burden of disease (GBD) data to understand the burden of CRC attributable to low whole-grain diets is crucial for informing public health policies aimed at reducing CRC-related burdens.MethodsThis study utilized data from the GBD 2021 to analyze global trends in mortality and disability-adjusted life years (DALYs) attributable to low whole-grain diets from 1990–2021. A Bayesian age-period-cohort (BAPC) model was employed to project the future burden of CRC attributable to low whole-grain diets up to 2050.ResultsIn 2021, the global number of deaths attributable to low whole-grain diets was 186,256.80, representing an 82.94% increase from 1990. The number of global DALYs attributable to low whole-grain diets in 2021 was 4,327,218.86, a 70.30% increase from 1990. The burden of CRC in males attributable to low whole-grain diets was greater than that in females aged 50–74 years. Nationally, Monaco recorded the highest mortality rate (13.23/100,000), China had peak deaths/DALYs. Projections to 2050, the global number of deaths attributable to low whole-grain diets will continue to rise, reaching 199,565.06.ConclusionsLow whole-grain diets pose a significant threat to public health, contributing to an increasing burden of CRC. To reduce the burden of CRC attributable to low whole-grain diets, enhancing public education and awareness of whole-grain diets, implementing policies to promote the consumption of whole grains, and conducting early screening among high-risk populations are recommended.